Impact of Using Simulink in Matlab on Students` Academic Achievement and Gender in Elctronics Works Trade in Technical Colleges of Adamawa State, Nigeria (Global Journal of Human-Social Science, 2021)
This study explored the impact of using Simulink in MATLAB on Students Academic Achievement and Gender in Electronics Works Trade in Technical Colleges of Adamawa State Nigeria The study adopted quasi-experimental design Two research questions and two hypotheses guided the study The population of the study was made up of all NTC students offering Electronics works Trades course in Adamawa state Technical Colleges Purposive sampling was used to select 52 NTC II students offering Electrical Works Trade from Yola South and Numan Technical colleges The instrument for data collection named Electronics Works Trade Achievement Test EWTAT was constructed validated and used for the study The reliability of EWTAT was determined using Pearson Product Moment Correlation Statistic PPMCS and it yielded 0 70 Mean statistics was used to answer the two research questions and t-test statistic techniques was used for testing the null hypotheses at 0 05 level of significance findings of the study revealed that using Simulink in MATLAB was more effective for teaching Rectifier circuits in Electronics Works Trade than when Lecture Method was used
Keywords: MATLAB; simulink; simulation; academic achievement and electronic technology